On Transport Service Selection in Intermodal Rail/Road Distribution Networks - Christian Bierwirth; Thomas Kirschstein; Frank Meisel (BuR - Business Research, 2012)
Intermodal rail/road freight transport constitutes an alternative to long-haul road transport for the distribution of large volumes of goods. The paper introduces the intermodal transportation problem for the tactical planning of mode and service selection. In rail mode, shippers either book train capacity on a per-unit basis or charter block trains completely. Road mode is used for short-distance haulage to intermodal terminals and for direct shipments to customers. We analyze the competition of road and intermodal transportation with regard to freight consolidation and service cost on a model basis. The approach is applied to a distribution system of an industrial company serving customers in eastern Europe. The case study investigates the impact of transport cost and consolidation on the optimal modal split.
urn:nbn:de:0009-20-35067
Keywords: 650; intermodal transportation problem; service selection; transport cost rates; sustainable transport chain; Güterverkehr; Transportproblem; Unternehmensnetzwerk; Dienstleistungsqualität; Operations Research